Social Portrait of the Family in the Light of New Socio-Political Trends - Gabisheva, Lyudmila K. (2022)
The issue regarding formation of a values-based attitude towards creating a family among modern youth is acquiring special relevance, since changes in moral guidelines have led to the intensification of negative phenomena such as: liberalisation of sexual morality, an increased number of divorces, illegitimate births, single-parent families, and the spread of social orphanhood. Due to the fact that the family is currently perceived as a structural component of the development of individual socio-economic trends, the purpose of the paper is to assess the levels of values-based attitudes towards family creation among students. In the course of the study, the following methods were used: diagnostic (questionnaires, the method of sentence completion, testing), that made it possible to identify the levels of formation of the attitude towards family creation among students; a theoretical method of analysis that allows a comprehensive study of the reasons that complicate the process of forming a values-based attitude regarding family creation. The novelty of the study is determined by the fact that a student family is understood as a family in which both spouses are full-time students of a higher education institution, that is, homogeneous in social status of a man and a woman. This is a young family in which the spouses are no more than 28 years old, and the length of family life does not exceed 5 years. The paper indicates that student families are the most progressive, since spouses are ready to accept everything new - in the organisation of life, in the arrangement of the family structure, and the like. Material motives in choosing a spouse in such families play a secondary role, especially in relation to the requirements from a woman to a man. The materials of the paper are of practical value for experimental verification of pedagogical conditions for the family creation among students in extracurricular activities